Role of Environmental Confounding in the Association between FKBP5 and First-Episode Psychosis - Ajnakina, Olesya; Borges, Susana; Di Forti, Marta; Patel, Yogen; Xu, Xiaohui; Green, Priscilla; Stilo, Simona A.; Kolliakou, Anna; Sood, Poonam; Marques, Tiago Reis; David, Anthony S.; Prata, Diana; et al. (Frontiers in Psychiatry, 2014)
Background: Failure to account for the etiological diversity that typically occurs in psychiatric cohorts may increase the potential for confounding, as a proportion of genetic variance will be specific to exposures that have variable distribution in cases. This study investigated whether minimizing the potential for such confounding strengthened the evidence for a genetic candidate currently unsupported at the genome-wide level. Methods: 291 first-episode psychosis cases from South London UK, and 218 unaffected controls were evaluated for a functional polymorphism at the rs1360780 locus in FKBP5. The relationship between FKBP5 and psychosis was modelled using logistic regression. Cannabis use (Cannabis Experiences Questionnaire) and parental separation (Childhood Experience of Care and Abuse Questionnaire) were modelled as confounders in the analysis. Results: Association at rs1360780 was not detected until the effects of the two environmental factors had been adjusted for in the model (OR=2.81, 95% CI 1.23-6.43, p=0.02). A statistical interaction between rs1360780 and parental separation was confirmed by stratified tests (OR=2.8, p=0.02 vs. OR=0.89, p=0.80). The genetic main effect was directionally-consistent with findings in other (stress-related) clinical phenotypes. Moreover, the variation in effect magnitude was explained by the level of power associated with different cannabis constructs used in the model (r=0.95). Conclusions: Our results suggest that the extent to which genetic variants in FKBP5 can influence susceptibility to psychosis may depend on the other etiological factors involved. This finding requires further validation in other large independent cohorts. Potentially this work could have translational implications, as the ability to discriminate between genetic etiologies, based on a case-by-case understanding of exposure history would confer an important clinical advantage that would benefit the delivery of personalizable treatment strategies